STRATEGIC APPROACHES OF INTERNATIONAL HOTEL CHAINS TO ENTER ON THE ROMANIAN MARKET - Cosma Smaranda; Fleseriu Cristina (Annals of the University of Oradea: Economic Science, 2012)
On the Romanian market 23,9% of all accommodation structures are hotels. Among these 4% are belonging to international hotel chains which is a very small percentage. Almost all international hotel chains realized the potential of the market and that is why they intend to increase the number of hotels opened in Romania. Hotel chains attempt to control and dominate the market as result of an extremely dynamic and complex environment. The decision made by a hotel company to carry out its activity in a foreign country and the way to enter into the market can be motivated by many reasons. The paper analysis the presence of international hotel chains on the Romanian hospitality market and the strategies used to enter on the Romanian market compared with the global strategies. The paper used the comparison method to highlight different entry strategies used by international hotel chains when entering a foreign market. For data collection, the main method used was the observation of annual statistical reports with the support of international hotel chains. The first international hotel chain that came in Romania was InterContinental in 1971, but the majority entered on the Romanian market after 2000. In 2012 other chains announced the intension to penetrate this market. The study identifies strategies for penetrating the Romanian market by international hotel chains. The preferred penetration strategy on the Romanian market is management contract followed by franchise. Not least are highlighted comparative aspects of internationalization decisions taken by the chains in the world and in Romania, analyzing whether in Romania are predominantly used the same strategy as in most other countries or some specific strategies. International hotel companies want to entre on the Romanian market because they consider that in this area is need for hotels which belong to the luxury segment but also hotels that belong to the economy segment.